A Video-Assisted Thoracoscopic Approach to Transaxillary First Rib Resection. Issue 1 (January 2015) - Soukiasian, Harmik J.; Shouhed, Daniel; Serna-Gallgos, Derek; McKenna, Robert; Bairamian, Vahak J.; McKenna, Robert J.
<x xml:space="preserve">Abstract</x> Objective Thoracic outlet syndrome (TOS) can be associated with neurologic, arterial, or venous deficiencies. When nonsurgical treatment has failed to adequately palliate TOS, surgical intervention is indicated. The supraclavicular and transaxillary approaches are currently the most commonly used approaches for first rib resection, yet little has been reported to date on outcomes of minimally invasive procedures, such as video-assisted thoracoscopic surgery (VATS). The purpose of this article was to describe a minimally invasive approach to TOS and the associated outcomes. Methods This study is a retrospective analysis of a prospectively maintained database. Patients who failed nonsurgical therapy for TOS were referred to our practice for evaluation of surgery with a VATS minimally invasive first rib resection. Between 2001 and 2010, 66 VATS procedures were performed on 58 patients (41 women, 17 men). Patients were followed postoperatively for a mean time of 13.5 months. Results Forty-one patients were women (70.7%), and the mean age was 40.5 years, with a patient age range of 17 to 59 years. The mean length of hospital stay was 2.47 days; median length of stay was 2 days. There were a total of eight complications (12.1%). There were no mortalities. Conclusions Video-assisted thoracoscopic surgery first rib resection for TOS is another feasible option for TOS, which can be added to the armamentarium of the thoracic surgeon. The outcomes associated with our technique are comparable with the outcomes related to other current standards of care.